ANALYSIS OF FACTORS THAT MAY AFFECT THE PERFORMANCE OF ACCOUNTING INFORMATION SYSTEMS AT PT. PAWNTOWN(PERSERO) REGIONAL OFFICE I MEDAN - Dita Syafira; Hernawaty Hernawaty; Ahmad Fadlan (Proceeding of The International Conference on Economics and Business, 2022)
Research conducted at PT. Pegadaian (Persero) Medan Regional Office I aims to determine the influence of the factors that make the performance of the Accounting Information System quality. The research method was carried out with an associative quantitative approach. The research data was obtained by distributing questionnaires to 50 employees of the company who were sampled. Data processing was carried out with the help of the SPSS Version 22 application. Data analysis was carried out using multiple linear regression approaches, partial tests, simultaneous tests, and determination tests. The conclusions from this study indicate that personal technical skills, top management support, user involvement in developing systems, education and training programs, partially have a positive and not significant effect on the performance of accounting information systems at PT. Pegadaian (Persero) Regional Office I Medan, while the existence of the Steering Committee has a positive and significant effect on the performance of the Accounting Information System at PT. Pegadaian (Persero) Regional Office I Medan. Simultaneously personal technical skills, Top Management support, user involvement in developing systems, education and training programs, and the existence of the Steering Committee have a positive and significant effect on the performance of the accounting information system at PT. Pegadaian (Persero) Regional Office I Medan.